Knowledge-intensive business services as an element of learning regions - the case of Baden-Wurttemberg - Simone Strambach (European Regional Science Association (ERSA), 1998)
In the globalizing process, the production of knowledge and the management of information gain increasing strategic importance for the competitiveness of regions. Theoretical conceptions of the learning economy and the learning region emphasise that the capability to learn is crucial for the economic success of firms, regions and national economies. Given this background, the proposal will focus on the significance of knowledge?intensive business services for innovation and learning. So far, knowledge about innovative activities of service firms and their significance in the technological change is existent only to a low extent. For a long time, research concerning technological change as well as innovations focussed on the manufacturing industry and the development and transfer of technological knowledge. The dynamic growth of business?related services has now been documented in numerous studies not only in Germany, but also in other European countries. Their role in innovativeness and competitiveness in the current situation of structural change has, however, received little attention. A major reason is that it is very difficult to establish the quantitative contribution these services make to innovation at both the macro and micro levels. The present state of the statistics for services and innovation make it impossible to determine what the contribution is. From a qualitative point of view, however, this service segment is an important element in the innovation system. The contribution of knowledge?intensive business service firms to innovation is not just the result of their own innovative activities. It also results from the indirect and positive feedback effects which originate on the demand side as a result of the use of the services by client firms. The speech will focus on specific development trends of knowledge?intensive business services in the regional innovation system of Baden?Wuerttemberg, and the role of these services in the present regional restructuring process will be examined.
Keywords: 330